2001
DOI: 10.1038/ncb0901-816
|View full text |Cite
|
Sign up to set email alerts
|

UDP–sugar transporter implicated in glycosylation and processing of Notch

Abstract: Glycosylation modifies protein activities in various biological processes. Here, we report the functions of a novel UDP-sugar transporter (UST74C, an alternative name for Fringe connection (Frc)) localized to the Golgi apparatus in cellular signalling of Drosophila. Mutants in the frc gene exhibit phenotypes resembling wingless and Notch mutants. Both Fringe-dependent and Fringe-independent Notch pathways are affected, and both glycosylation and proteolytic maturation of Notch are defective in mutant larvae. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 49 publications
5
92
0
Order By: Relevance
“…The interaction of the Notch receptor with its ligands, Serrate and Delta, is modulated by the addition of GlcNAc to an O-linked Fuc on the Notch by FRINGE enzyme (30 -33). In Drosophila, mutation of frc leads to a defect in Notch maturation (10). Here, HFRC1 exhibited an apparent K m value for UDP-GlcNAc comparable with that of FRC (8 versus 7.8 M, respectively).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The interaction of the Notch receptor with its ligands, Serrate and Delta, is modulated by the addition of GlcNAc to an O-linked Fuc on the Notch by FRINGE enzyme (30 -33). In Drosophila, mutation of frc leads to a defect in Notch maturation (10). Here, HFRC1 exhibited an apparent K m value for UDP-GlcNAc comparable with that of FRC (8 versus 7.8 M, respectively).…”
Section: Discussionmentioning
confidence: 77%
“…Biochemical analysis of sqv-7 mutants has demonstrated defects in both chondroitin and heparan sulfate biosynthesis in vivo (8). Furthermore, Selva et al (9) and Goto et al (10) reported that the Drosophila melanogaster gene of fringe connection (frc) is involved in embryonic Wingless/Hedgehog and fibroblast growth factor signaling (9,10). Frc encodes a multisubstrate-specific NST that transfers UDP-sugars into the Golgi apparatus (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This set of strains has been used to identify a new gene involved in Notch signaling (Goto et al, 2001), and detailed analyses of the adult brain and embryonic PNS are under way (Tanaka et al, in prep; Uemura et al, in preparation). Most of the strains will be available from the Genetic Strain Research Center of NIG and from the Drosophila Genetic Resource Center, Kyoto Institute of Technology, and are expected to serve as valuable tools for the research community.…”
Section: Fig 2 Examples Of Expression Patterns Of P{gawb} Enhancer mentioning
confidence: 99%
“…This gene encodes a sugar-transporter protein and has a role in the glycosylation of proteins that are expressed in the surface of cells (Selva et al, 2001), and in some cases, in development by regulating the surface presentation of gylycospylated proteins involved in cell fate decisions (Goto et al, 2001). Further clues into the function of Slc35d3 come from mice who carry inactivated copies of the gene and show striatal and motor abnormalities (Lu et al, 2008).…”
Section: Identification Of Novel Striatonigral and Striatopallidal Genesmentioning
confidence: 99%